The Existence of Decisions of Customary Institutions in the Settlement of Criminal Cases in Indonesia - ., Kuntadi (KnE Social Sciences, 2023)
Article 5 paragraph (1), Article 10 paragraph (1), and Article 50 paragraph (1) of Law 48 of 2009 on Judicial Power paved the way for the recognition of customary criminal law, in which the existence of the adapt community and adapt law is recognized and guaranteed by the constitution. However, since customary criminal law is based on the philosophy of harmony and cosmic balance within society, it would be difficult to find common ground regarding the principle of legality within the Criminal Code. This study aims to identify the influence of customary institution decisions in criminal case proceedings. This research uses a socio-legal methodology that has descriptive and analytical characteristics. This research uses qualitative interactional analysis. The results of this study indicate that, prior to the enactment of Prosecutors’ Regulations on Restorative Justice, the customary institution decision has cemented its existence as a source of law to decide criminal cases. The enactment of Prosecutors’ Regulations on Restorative Justice has shifted it into one of the reasons for the public prosecutor to consider dropping criminal charges based on restorative justice. The regulation will require the involvement of community leaders or representatives to terminate criminal proceedings. Keywords: customary institutions, customary law, criminal cases, restorative justice